Factors Influencing Success and Failure of Health Informatics Systems - Brender, J.; Ammenwerth, E.; Nykänen, P.; Talmon, J. (Methods of Information in Medicine, 2006)
Objectives: The aim is to gain information on factors influencing success and failure for Health Informatics applications from a group of medical informaticians.Methods: Based on the presentations at a special topic conference on success and failure in Health ICT and analysis of the proceedings, we conducted a Delphi study on success and failure aspects.Results: A total of 110 success factors and 27 failure criteria were identified, distributed on categories like functional, organizational, behavioral, technical, managerial, political, cultural, legal, strategy, economy, education and user acceptance. These factors and criteria were rated for six different system types. Unanimously it was agreed that “collaboration and co-operation” and “setting goals and courses” are “essential for the success” of clinical systems, and “user acceptance” for educational systems. Similarly, the score “essential in order to avoid a failure” were given unanimously on clinical systems for “response rate and other performance measures” and on administrative systems for “not understanding the organizational context” with “not understanding or foreseeing the extent to which the new IT-system affects the organization, its structure and/or work procedures” as the highest scoring sub-item.Conclusions: All success factors and failure criteria were considered relevant by the Delphi expert panel. There is no small set of relevant factors or indicators, but success or failure of a Health ICT depends on a large set of issues. Further, clinical systems and decision support systems depend on more factors than other systems.
Keywords: Success; failure; systems development; Delphi